An Experiment in Interdisciplinary STEM Education: Insights from the Catholic Intellectual Tradition - Fr. Joseph R. Laracy; Thomas Marlowe; Fr. Gerald J. Buonopane (Journal of Systemics, Cybernetics and Informatics, 2017)

(untitled)
The "silo effect" is a major problem today in academia, i.e. the growing tendency of disciplinary isolation both in research and teaching. "Siloing" is noted particularly in the formal, natural, and applied sciences. Yet, many areas of human inquiry require by their very nature, an interdisciplinary approach. At Seton Hall University, in the context of the Core Curriculum for undergraduate studies, serious efforts are underway to bring the sciences into dialogue with the wider Catholic intellectual tradition. By fostering a healthy exchange between philosophy, theology, mathematics, computing, and the natural sciences, upperclassmen have been able to explore topics of great personal interest and draw significant connections from content learned in diverse fields of their education. Opportunities exist to extend and adapt this approach to other university settings internationally.